2013
DOI: 10.1097/mnh.0b013e328365ba53
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of catheter lock solutions

Abstract: The ideal catheter lock solution would be one that prevents infections and thrombosis safely and effectively, while being economically viable. Recent developments have led to improvements in the development of catheter locking solutions, but the search for the perfect 'solution' is still ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
0
16
0
1
Order By: Relevance
“…Various measures have been studied for the prevention of CR-BSI, one of which is the use of lock solutions (Katneni and Hedayati, 2007;Böhlke et al, 2015). This measure consists of instilling solutions with antithrombotic and antimicrobial properties into the catheter lumen at concentrations 100-1000 times greater than the minimum inhibitory concentration commonly used for systemic therapy, in an attempt to prevent the main mechanisms of morbidity and mortality associated with central venous catheters (CVCs): dysfunction due to thrombosis and infection (Katneni and Hedayati, 2007;Böhlke et al, 2015;Betjes, 2011;Niyyar and Lock, 2013;Labriola and Pochet, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various measures have been studied for the prevention of CR-BSI, one of which is the use of lock solutions (Katneni and Hedayati, 2007;Böhlke et al, 2015). This measure consists of instilling solutions with antithrombotic and antimicrobial properties into the catheter lumen at concentrations 100-1000 times greater than the minimum inhibitory concentration commonly used for systemic therapy, in an attempt to prevent the main mechanisms of morbidity and mortality associated with central venous catheters (CVCs): dysfunction due to thrombosis and infection (Katneni and Hedayati, 2007;Böhlke et al, 2015;Betjes, 2011;Niyyar and Lock, 2013;Labriola and Pochet, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications have reported the emergence of antibiotic/ antimicrobial-resistant bacteremia in HD patients. One way to solve this problem is to use non-antibiotic antimicrobial catheter locks, such as those with high concentrations of citrate and taurolidine, which are able to eradicate biofilms and have broadspectrum activity against both gram-positive and gram-negative organisms enclosed in biofilms generated in vivo (Katneni and Hedayati, 2007;Böhlke et al, 2015;Betjes, 2011;Niyyar and Lock, 2013;Labriola and Pochet, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with antibiotics at concentrations 1,000-fold above the systemic therapeutic dose, current ALT may be ineffective in eradicating mature bacterial and fungal biofilms (4-7). In addition, leakage of antimicrobial lock solutions into the bloodstream has been implicated in systemic toxicity in patients with long-term CVCs, potential for increased biofilm formation, as well as adverse effects on the catheter integrity and intraluminal precipitation (5-6,8-9).…”
Section: Introductionmentioning
confidence: 99%
“…After three decades of optimizing their utility in catheter lock solutions, reliance on current antibiotics is fundamentally challenged by the limited scope to improve the trade-off between efficacy and toxicity (6,7,10) and by the potential risk of antimicrobial resistance (11). Inspired by the way that endogenous reactive oxygen species (ROS) are released by immune cells of a mammalian host to inactivate invading bacteria, extensive studies have shown that exogenous reactive oxygen and nitrogen species (RONS) and other antimicrobial effectors (e.g.…”
Section: Introductionmentioning
confidence: 99%